Terrestrial and marine Antarctic fungi extracts active against Xanthomonas citri subsp. citri - Vieira, G. [UNESP]; Purić, J. [UNESP]; Morão, L. G. [UNESP]; dos Santos, J. A. [UNESP]; Inforsato, F. J. [UNESP]; Sette, L. D. [UNESP]; Ferreira, H. [UNESP]; Sass, D. C. [UNESP] (My University, 2018)
This study aims to obtain secondary metabolites extracts from filamentous fungi isolated from soil and marine sediments from Antarctica and assess its potential antibacterial activity on Xanthomonas citri subsp. citri, the agent of citrus canker. Metabolites production was conducted in Malt 2% broth at 15°C for 20 days after which intracellular and extracellular extracts were obtained. The extracts were evaluated by cell viability assays through Resazurin Microtitre Assay. From 158 fungal extracts, 33 hampered bacterial growth in vitro. The average inhibition of the extracts obtained from terrestrial (soil) and marine (sediments) fungi was 94 and 97% respectively. These inhibition values were close to the average of 90% cell death for the positive control. MIC90 and MBC for the bioactive extracts were established. Isolates that produced active metabolites against the phytopathogen were identified using molecular taxonomy (ITS-rRNA sequencing) as: Pseudogymnoascus, Penicillium, Cadophora, Paraconiothyrium and Toxicocladosporium. Antarctic fungal strains isolated from terrestrial and marine sediments were able to produce secondary metabolites with antimicrobial activity against X. citri subsp. citri, highlighting the importance of these microbial genetic resources. These metabolites have potential to be used as alternatives for the control of this plant pathogen. Significance and Impact of the Study: This manuscript makes an impact on the study of micro-organisms from extreme habitats and their possible contribution in discovering new active molecules against pathogens of agricultural interest. Studies on the Antarctic continent and its communities have attracted the scientific community due to the long period of isolation and low levels of disturbance that surrounds the region. Knowing the potential of fungi in this region to produce active secondary metabolites, we aim to contribute to the discovery of compounds with antibacterial action in Xanthomonas citri subsp. citri, a plant pathogen present in several regions around the globe.
Keywords: Antarctic fungi; antibacterial action; citrus canker; secondary metabolites; Xanthomonas